Considerations for mass gatherings in the context of COVID-19: Annex: Considerations in adjusting public health and social measures in the context of COVID-19 (WHO, 2020)
WHO guidance document that provides advice on adjusting public health and social measures, while managing the risk of resurgence of COVID-19 cases. A series of annexes has been developed to guide countries through adjusting public health and social measures in different contexts. The purpose of this annex is to provide key considerations to health authorities and event organizers for reopening mass gatherings (MG); it should be read in conjunction with the interim guidance (1).